h - Schomburg, Dietmar; Schomburg, Ida.; Chang, Antje; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Springer Handbook of Enzymes provides data on enzymes sufficiently well characterized. It offers concise and complete descriptions of some 5,000 enzymes and their application areas. Data sheets are arranged in their EC-Number sequence and the volumes themselves are arranged according to enzyme classes. This new, second edition reflects considerable progress in enzymology: many enzymes are newly classified or reclassified. Each entry is correlated with references and one or more source organisms. New datafields are created: application and engineering (for the properties of enzymes where the sequence has been changed). The total amount of material contained in the Handbook has more than doubled so that the complete second edition consists of 39 volumes as well as a Synonym Index. In addition, starting in 2009, all newly classified enzymes are treated in Supplement Volumes. Springer Handbook of Enzymes is an ideal source of information for researchers in biochemistry, biotechnology, organic and analytical chemistry, and food sciences, as well as for medicinal applications.
Acetylenedicarboxylate decarboxylase -- Sulfopyruvate decarboxylase -- 4-Hydroxyphenylpyruvate decarboxylase -- Threonine-phosphate decarboxylase -- Phosphonopyruvate decarboxylase -- 4-Hydroxyphenylacetate decarboxylase -- D-Dopachrome decarboxylase -- 3-Dehydro-L-gulonate-6-phosphate decarboxylase -- Diaminobutyrate decarboxylase -- Vanillin synthase -- D-Threonine aldolase -- 1-Deoxy-D-xylulose 5-phosphate synthase -- Aminodeoxychorismate lyase -- 4-Hydroxy-2-oxovalerate aldolase -- Chorismate lyase -- Aristolochene synthase -- Pinene synthase -- Myrcene synthase -- (?)-(4S)-Limonene synthase -- Benzylsuccinate synthase -- 3,4-Dihydroxy-2-butanone-4-phosphate synthase -- Cyclohexa-1,5-dienecarbonyl-CoA hydratase -- trans-Feruloyl-CoA hydratase -- Cyclohexa-1,5-dienecarbonyl-CoA hydratase -- Cyclohexyl-isocyanide hydratase -- Cyanase -- 2-Hydroxyisoflavanone dehydratase -- Bile-acid 7?-dehydratase -- 3?,7?,12?-Trihydroxy-5?-cholest-24-enoyl-CoA hydratase -- Ectoine synthase -- Methylthioribulose 1-phosphate dehydratase -- Aldos-2-ulose dehydratase -- 1,5-Anhydro-D-fructose dehydratase -- Acetylene hydratase -- o-succinylbenzoate synthase -- Glucuronan lyase -- Anhydrosialidase -- Levan fructotransferase (DFA-IV-forming) -- Inulin fructotransferase (DFA-I-forming) -- Inulin fructotransferase (DFA-III-forming) -- Chondroitin B lyase -- Chondroitin-sulfate-ABC endolyase -- Chondroitin-sulfate-ABC exolyase -- Pectate trisaccharide-lyase -- Threonine synthase -- Ethanolamine-phosphate phospho-lyase -- Methylglyoxal synthase -- 3-Dehydroquinate synthase -- Chorismate synthase -- Pentalenene synthase -- Casbene synthase -- Aristolochene synthase -- (?)-Endo-fenchol synthase -- Sabinene-hydrate synthase -- 6-Pyruvoyltetrahydropterin synthase -- (+)-?-Cadinene synthase -- Pinene synthase -- Myrcene synthase -- (4S)-Limonene synthase -- Taxadiene synthase -- Abietadiene synthase -- ent-Kaurene synthase -- (R)-Limonene synthase -- Vetispiradiene synthase -- Germacradienol synthase -- Germacrene-A synthase -- Amorpha-4,11-diene synthase -- S-Linalool synthase -- R-Linalool synthase -- Isoprene synthase -- 2-Hydroxypropyl-CoM lyase -- threo-3-Hydroxyaspartate ammonia-lyase -- L-Serine ammonia-lyase -- D-Serine ammonia-lyase -- Threonine ammonia-lyase -- erythro-3-Hydroxyaspartate ammonia-lyase -- Aminodeoxygluconate ammonia-lyase -- 3,4-Dihydroxyphenylalanine reductive deaminase -- Deacetylisoipecoside synthase -- Deacetylipecoside synthase -- Prenylcysteine lyase -- Phosphosulfolactate synthase -- Leukotriene-C4 synthase -- S-Ribosylhomocysteine lyase -- S-(Hydroxymethyl)glutathione synthase -- 2-Hydroxypropyl-CoM lyase -- Sulfolactate sulfo-lyase -- L-Cysteate sulfo-lyase -- 2-C-Methyl-D-erythritol 2,4-cyclodiphosphate synthase -- Phosphatidylinositol diacylglycerol-lyase -- Glycosylphosphatidylinositol diacylglycerollyase -- FAD-AMP lyase (cyclizing) -- Sirohydrochlorin cobaltochelatase -- Sirohydrochlorin ferrochelatase -- Aliphatic aldoxime dehydratase -- Indoleacetaldoxime dehydratase -- Phenylacetaldoxime dehydratase -- Isopenicillin-N epimerase -- Serine racemase -- Maltose epimerase -- L-Ribulose-5-phosphate 3-epimerase -- UDP-2,3-Diacetamido-2,3-dideoxyglucuronic acid 2-epimerase -- Polyenoic fatty acid isomerase -- trans-2-Decenoyl-[acyl-carrier protein] isomerase -- Ascopyrone tautomerase -- Capsanthin/capsorubin synthase -- Neoxanthin synthase -- Phosphoglucosamine mutase -- (Hydroxyamino)benzene mutase -- Isochorismate synthase -- 3-(Hydroxyamino)phenol mutase -- Squalene-hopene cyclase -- 5-(Carboxyamino)imidazole ribonucleotide mutase -- Copalyl diphosphate synthase -- Ent-copalyl diphosphate synthase -- Aspartate-tRNAAsn ligase -- Glutamate-tRNAGln ligase -- Lysine-tRNAPyl ligase -- Pyrrolysine-tRNAPyl ligase -- trans-Feruloyl-CoA synthase -- Adenosylcobinamide-phosphate synthase -- Glutamate-putrescine ligase -- D-Aspartate ligase -- N-(5-Amino-5-carboxypentanoyl)-L-cysteinyl-D-valine synthase -- Aerobactin synthase -- L-Amino-acid ?-ligase -- Cyanophycin synthase (L-aspartate-adding) -- Cyanophycin synthase (L-arginine-adding) -- (Carboxyethyl)arginine ?-lactam-synthase -- 5-(Carboxyamino)imidazole ribonucleotide synthase -- Asparaginyl-tRNA synthase (glutaminehydrolysing) -- Glutaminyl-tRNA synthase (glutaminehydrolysing) -- Aminodeoxychorismate synthase -- Hydrogenobyrinic acid a,c-diamide synthase (glutamine-hydrolysing) -- Adenosylcobyric acid synthase (glutaminehydrolysing) -- Acetone carboxylase -- 2-Oxoglutarate carboxylase -- Magnesium chelatase -- Cobaltochelatase.
Keywords: Life sciences; Medicine; Toxicology; Biotechnology; Food science; Veterinary medicine; Biochemistry; Life Sciences; Biochemistry, general; Molecular Medicine; Pharmacology/Toxicology.; Food Science; Biotechnology; Veterinary Medicine